THE EFFECTS OF ADOPTION ON INHERITANCE RIGHTS ACCORDING TO THE SERBIAN CIVIL CODE - Jančić Mihić, Melanija (ACADEMIC REVIEW, 2024)
In modern legal systems, among which is the positive law of the Republic of Serbia, the institution of adoption is established, primarily in order to insure the protection of a child without parental care. From the legal point of view, the main aim of adoption is, therefore, child protection. This especially applies to legal systems that have legally recognized only the institution of full adoption in their national legislation. Considering basic goal of full adoption, which is the complete integration of the adoptee into the adopter’s family, establishing mutual kinship relations in full and breaking all legal ties between the adoptee and its biological family, more specifically its biological parents and all relatives, the establishment of full adoption is of great importance in inheritance law. However, the institution of full adoption has not always been the only way of establishing adoptive kinship in Serbian law. Consequently, adoptive kinship, as a legally relevant fact when applying rules of intestate succession, had different effects in inheritance law with respect to the form of adoption. Thus, the aim of this article is to analyze the provisions of the Serbian Civil Code from 1844, in order to provide a comparative overview of the importance of the effects of adoption on inheritance rights using the historical method and indicating the current Serbian legislation on adoption in the field of inheritance.